The relation between knowledge and concern: A global study of children and COVID-19 - Dina L. G. Borzekowski; Christopher R. Lane; Ankit Chandnani; Maya Götz (Health Psychology Research)
COVID-19 messages vary around the world, and populations receive these messages in different ways. Children are a vulnerable audience, especially in terms of risk communication. As messages are being developed, communicated, and disseminated about this pandemic, it is important to know the relation between COVID-19 knowledge and concern among preadolescents. In Spring 2020, children (_N_= 4,249) from 8 global regions completed an online survey (_Mage_= 11.0, 54% female, 46% male). We assessed children's COVID-19 knowledge by asking about prevention and symptoms, as well as myths about the virus. We also assessed children's concerns by asking about worries about self and others getting sick, missing school, and interruption of activities. Our analyses revealed different relations between knowledge and concern by region. Among children from Sub-Saharan Africa, the Arabian region, Asia, and North America, there was a positive relation between knowledge and concern. For those from Latin America, Oceania, Europe, and Southeast Asia, the relation was flat or negative. When producing messages for children during a public health crisis, health communicators must know that more knowledge is not always associated with less concern.